دور قطاع التأمين في النشاط الاقتصادي - شريقي طرفة; محمد رافـد (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يعد قطاع التأمين من أهم قطاعات الخدمات المالية في العالم، و يواكب مجمل الأنشطة الاقتصادية الأخرى ويسهم في دعمها والمحافظة على استقرارها. تهدف دراستنا إلى استعراض هذا الدور الهام للتأمين في النشاط الاقتصادي، وموقع هذا القطاع في الاقتصاد الوطني لبعض دول العالم. نصل من خلال هذه الدراسة إلى تحديد بعض الأوجه التي يؤثر من خلالها التأمين في النشاط الاقتصادي خاصة في الصناعة والزراعة، إضافة إلى إيضاح موقع قطاع التأمين في اقتصاد بعض دول العالم وارتباط تطور هذا القطاع بالتطور الاقتصادي العام في تلك الدول، محاولين بذلك الوصول إلى توصيات موضوعية قابلة للتطبيق العملي، تسهم بتنمية وتطوير هذا القطاع في سورية. The insurance sector is considered one of the most important pillars of world financial services. It accompanies, supports and helps in stabilizing other economic activities. This study tries to illustrate the important role of insurance in the economic activity, and its position in national economies around the world. In this study we try to define some aspects in insurance, which affect the economic activity, especially in industry and agriculture sectors, in addition to the illustration of the insurance position in the economic of some countries, and the involvement of this sector’s development with the general economic evolution in these countries, trying to reach applicable objective recommendation that contributes in the development of this sector in Syria.